Theories of Visual Attention - linking cognition, neuropsychology, and neurophysiology - Signe Allerup Vangkilde (Frontiers Research Topics, 2015)
The Neural Theory of Visual Attention of Bundesen, Habekost, and Kyllingsbæk (2005) was proposed as a neural interpretation of Bundesen's (1990) theory of visual attention (TVA). In NTVA, visual attention functions via two mechanisms: by dynamic remapping of receptive fields of cortical cells such that more cells are devoted to behaviorally important objects than to less important ones (filtering) and by multiplicative scaling of the level of activation in cells coding for particular features (pigeonholing). NTVA accounts for a wide range of known attentional effects in human performance and a wide range of effects observed in firing rates of single cells in the primate visual system and thus provides a mathematical framework to unify the 2 fields of research. In this Research Topic of Frontiers in Psychology, some of the leading theories of visual attention at both the cognitive, neuropsychological, and neurophysiological levels are presented and evaluated. In addition, the Research Topic encompasses application of the framework of NTVA to various patient populations and to neuroimaging as well as genetic and psychopharmacological studies.